Prawybory we francuskich partiach politycznych jako mechanizm wyłaniania kandydatów do prezydentury na przykładzie Republikanów i Partii Socjalistycznej - Łukasz Jakubiak (Politeja, 2022)
PRIMARY ELECTIONS IN FRENCH POLITICAL PARTIES AS A MECHANISM FOR SELECTING CANDIDATES FOR THE PRESIDENCY ON THE EXAMPLE OF THE REPUBLICANS AND THE SOCIALIST PARTY